Impact of Self-Regulated Learning Behavior on the Academic Achievement of Saudi Undergraduates - د. علياء عمر علي المروعي; د. ندى حميد حسين الحجي (مجلة العلوم التربوية والنفسية, 2025)
In an era where academic success is paramount, understanding the strategies that underpin effective learning is crucial. Self-regulated learning (SRL) behavior is one of the self-learning behaviors that students utilize to incorporate significant differences in their academic performances. The research study aims to analyze the impact of self-regulated learning behavior on the educational achievement of Saudi undergraduates. A quantitative method was employed to analyze the data using descriptive and inferential methods. The study adopted an online questionnaire to collect data from undergraduate students in the Natural Sciences and English course in the western region of Saudi Arabia. The data was collected through an online survey questionnaire (OSLQ). Cronbach's alpha value for the reliability of the questionnaire was 0.90. The data consisted of 404 respondents’ online filled questionnaires after piloting. ANOVA and regression tests were applied to analyze the data. The result of the study indicates a significant difference in the academic achievement of respondents with different Self-Regulated Learning (SLR) levels (F= 83.662, p < 0.05). The study concluded that SRL skills make a significant contribution to enhancing students' academic achievement.